ENGINEERING DEVELOPMENT OF TELESCOPE CONTROL SYSTEMS - Ivanov, V. N.; Ryabov, A. V.; Paulin, L. S.; Pereversentsev, A. F.; Arkhipov, M. G. (Одеські астрономічні публікації, 2017)
The engineering development of some variants of computer aided (automatic) control systems is presented for moderate telescopes with step-by-step drives as duty elements and with pulse sensors of BE-198 type as angular sensors.